Ex-ante profitability of animal traction investments in semi-arid sub-Saharan Africa: Evidence from Niger and Nigeria - Jansen, G.P. (Elsevier, 1993)
Adoption of animal traction in sub-Saharan Africa has historically been slow and stagnant. This is despite considerable efforts by researchers and development planners to introduce the technique among smallholder semi-subsistence farmers in a large number of countries. Based on a simulation model, this study uses a capital budgeting approach to investigate the profitability of animal traction relative to manual cultivation in two semi-arid regions of sub-Saharan Africa. Data from a number of cropping systems in western Niger and northern Nigeria are used to calculate present values of incremental returns together with internal rates of return on capital invested. The results show that animal traction is not profitable under many smallholders' actual conditions. For a millet-only farmer in Niger, ox traction yields insufficient returns and donkey traction is attractive only when sufficient amount of capital are available to include a cart in the investment package. Similarly, in a millet-cowpea systems, both ox traction and donkey traction yield acceptable returns only with a cart. In northern Nigeria, where relatively few donkeys are used for work, ox traction investments are profitable only with subsidised credit. However, profitability of animal traction investments in both Niger and Nigeria depends critically on the availability of fallow land. When a closed or nearly closed land frontier effectively limits the scope for area increases, returns on animal traction investments generally fall below critical levels. Adoption of animal traction technologies is likely to be increased by the development and dissemination of cheaper implements in Niger and a cheaper cart in Nigeria.